Medical office professionals a practical career guide - Santore, Marcia, 1960- (Practical career guides., 2019)
Medical Office Professionals includes interviews with professionals in the field, and covers careers that have proven to be stable, lucrative, and growing professions. Nurse Practitioner Physician's Assistant Medical Office Transcriptionist Phlebotomist Surgical Technician Pharmacy Technician Optometry Sonographer. Surgical Technologist.